Web scraping with Python : collecting data from the modern web - Mitchell, Ryan (Ryan E.) (Sebastopol, CA : O'Reilly Media, 2015)
Learn web scraping and crawling techniques to access data from any web source in any format. Teaches basic web scraping mechanics, but also delves into more advanced topics, such as analyzing raw data or using scrapers for frontend website testing.
Part I. Building scrapers: Your first web scraper -- Advanced HTML parsing -- Starting to crawl -- Using APIs -- Storing data -- Reading documents. Part II. Advanced scraping: Cleaning your dirty data -- Reading and writing natural languages -- Crawling through forms and logins -- Scraping JavaScript -- Image processing and text recognition -- Avoiding scraping traps -- Testing your website with scrapers -- Testing your website with scrapers -- Scraping remotely -- Python at a glance -- The internet at a glance -- The legalities and ethics of web scraping.
Includes index.
Keywords: Python (Computer program language); Data mining; Automatic data collection systems